Pop-Up Structures and the Fracture Pattern in the Balsam Lake Area, Southern Ontario - Rutty, Andrea; Cruden, Alexander (Géographie physique et Quaternaire, 1993)
ABSTRACTAn examination of topographic lineaments detectable in Landsat TM images and measurement of joints in outcrop in the Balsam Lake area reveals a systematic bedrock fracture pattern with three principal sets oriented 091°, 027°, and 152°. The 027° trend is parallel to a major aeromagnetic anomaly, the Niagara-Pickering Linear Zone (NPLZ), which underlies the Balsam Lake area and is thought to mark the sub-Paleozoic continuation of the Proterozoic Central Metasedimentary Belt Boundary Zone (CMBBZ). Possible origins of the main joint sets due to Acadian (091° set), Alleghanian (152° set) and St. Lawrence rift system tectonics (091° and 027° sets) are discussed. En-echelon pop-up structures have a mean principal trend of 118°. They displace Lake Algonquin paleobeaches, suggesting formation less than 12,500 years ago. The orientation of the pop-up structures is subnormal to the current in situ maximum horizontal stress direction, SHmax (020°), and is parallel to members of the 091° joint set, indicating possible nuclea-tion on favourably-oriented pre-existing joints. These pop-ups are the only features in the Balsam Lake area with strong evidence for a neotectonic age.